Jizzakh province general education in their school’s initial education quality indicators (2020-2023) - Bosimova Muazzam Baxtiyor kizi (Genius Publishing Group, 2023)
This article reflects on the work of general education schools in Jizzakh region
Keywords: Education; quality indicators; innovative news; school, teacher